Role of Ayurveda in the Prevention of Genetic Disorders (AYUSHDHARA, 2023)
Ayurveda is much more advanced in Genetic disorders from the ancient period. It emphasized on not only for disorders, as well as prevention too. Nowadays people concentrate more on Lifestyle disorders compared to Genetic disorders. A genetic disorder is caused by one or more abnormalities in the genome. As per WHO, Genetic disorders and congenital abnormalities occur in about 2% to 5% of all live births, accounting for upto 30% of paediatric hospital admissions and cause about 50% of childhood deaths in industrialized countries. The concepts were already mentioned by Acharyas in the context of Beeja (sperm and ovum), Beejabhaga (chromosomes) and Beejabhaga avayava (genes). They highlighted the concept of planning for better progeny, it starts even before marriage. Kulaja vikara’s are Asadhya by prognosis. When there is no therapeutic option, it is preferable to follow the Acharya's recommended precautions. Hence this study highlights the concept of Beeja, Beejabhaga, Beejabhaga-avayava dusti with special reference to the prevention of Genetic disorders.